The role of trust in budgeting processes and managerial performance: an empirical study in the local government of Aceh, Indonesia - Indriani, Mirna; Nadirsyah, Nadirsyah; M Daud, Rulfah (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study is to investigate a comprehensive model of the relationships between budget participation, procedural fairness, distributive fairness, managerial trust, goal commitment and managerial performance. The analysis using the structural equation model (SEM) is based on 347 individuals who are involved in the budgeting at Regional Apparatus Work Unit (SKPD) in Aceh Province, Indonesia. The results show that participation significantly influences procedural fairness which then managerial trust. Participation however do not influence distribution fairness. The findings also indicate that managerial trust influences budget goals commitment which subsequently enhances managerial performance. It also suggests that increased participation in budgeting fosters a sense of procedural fairness, which in turn increases managerial trust and budget goals commitment which enhances managerial performance. This study is useful in providing an input for local government to design an effective budget planning control process in which procedural fairness can be increased through participation in the process of budgeting and participation becomes a means in the process of increasing trust in management.